INFLUENCE OF THE CHOSEN TOPICS ON SPEAKING ACTIVITIES BY EFL STUDENTS AT UNIVERSITY OF PGRI RONGGOLAWE (UNIROW) TUBAN - Prasetyo, Kacung Heru; Panggabean, Christina IT; Wardhono, Agus (Universitas Muhammadiyah Gresik, 2017)
Speaking skill is one of important skills in learning English as Foreign Language. It is also the most difficult skill for EFL students. Therefore, the students should improve their speaking ability. One of the main ways is through the speaking activities. In fact, there are many factors that influence the success of EFL students’ speaking activities. One of the main factors is the chosen topics. In this study, the writer wants to know the kind of chosen topics which are used on speaking activities by EFL students, how far the influence of the chosen topics itself on speaking activities, and the reasons of choosing certain topics. The findings of this study present that most of EFL students tend to use the kind of topics of social, health, and culture. The chosen topics also have many influences on the EFL students’ speaking activities and their performance. The interesting topics especially about hot issues which happen in society can increase the students’ interest. Then, the best chosen topics make the EFL students’ speaking activities more interactive and successful. The favourite or interesting topics will also make the students more eager and do better on their speaking activities. Moreover, the EFL students choose certain topics for some reasons. Firstly, they are interested in the issues in the topic. Secondly, the EFL students use certain topics because they have their own experience about that topic. Thirdly, the EFL students tend to use hot issues in society to become their chosen topics on speaking activities. Finally, the EFL students use certain topics because they like a challenge; they also want to enhance their speaking ability, so they choose hard topics as their chosen topics on speaking activities.